2013
DOI: 10.1242/dev.100933
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated homologous recombination and subsequent genome modification in Drosophila

Abstract: Gene targeting by ‘ends-out’ homologous recombination enables the deletion of genomic sequences and concurrent introduction of exogenous DNA with base-pair precision without sequence constraint. In Drosophila, this powerful technique has remained laborious and hence seldom implemented. We describe a targeting vector and protocols that achieve this at high frequency and with very few false positives in Drosophila, either with a two-generation crossing scheme or by direct injection in embryos. The frequency of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
262
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(267 citation statements)
references
References 36 publications
3
262
0
2
Order By: Relevance
“…We next evaluated germ-line transmission of CRISPR/Casinduced mutations in wg and wls using nos-cas9. Nineteen randomly selected offspring of nos-cas9 U6:3-gRNA-wg flies were tested for wg mutations by genetic complementation with a previously characterized wg null allele (27). The wg null allele was not complemented in 12 of the 19 crosses, demonstrating efficient creation of nonfunctional wg mutations by CRISPR/Cas (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next evaluated germ-line transmission of CRISPR/Casinduced mutations in wg and wls using nos-cas9. Nineteen randomly selected offspring of nos-cas9 U6:3-gRNA-wg flies were tested for wg mutations by genetic complementation with a previously characterized wg null allele (27). The wg null allele was not complemented in 12 of the 19 crosses, demonstrating efficient creation of nonfunctional wg mutations by CRISPR/Cas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila it has been possible for several years to create specific genome modifications by HDR, although targeting typically occurs with very low efficiency (28). Recent studies have suggested that zinc finger, transcriptional activator-like effector (TALE), and Cas9 nucleases can increase the efficiency of HDR in flies, implying that the generation of site-specific DSBs is rate limiting (11,12,27,29,30). Therefore we tested whether the highly effective creation of DSBs by our transgenic CRISPR/Cas system could be exploited to facilitate efficient HDR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive libraries of P-element-based transposon insertions are available through stock centers, along with deletion and duplication lines [78][79][80][81]. Finally, targeted gene knock-out using optimized targeting plasmids in combination with CRISPR will greatly accelerate full KO coverage of the fly genome [82].…”
Section: Methods To Generate Immune Deficient Cells Tissues or Organmentioning
confidence: 99%
“…La validation fonctionnelle de cet élément a été réalisée d'une part in vitro, en démontrant une interaction physique directe, puis in vivo en suivant l'activation transcriptionnelle de dilp8 par Yki/ Sd. Dans le but de valider fonctionnellement le rôle de la voie Hippo dans le contrôle de dilp8, un mutant dilp8 a été généré par CRISPR/Cas9 [34,35] (➜). Les sites de fixation pour Sd/Yki dans le HRE endogène du promoteur dilp8 ont été mutés, créant ainsi un allèle du gène dilp8 insensible au contrôle transcriptionnel par Hippo/Yki.…”
Section: Coordination De La Croissance Entre Organes Et Robustesse Déunclassified